Direct block method for solving delay differential equations with initial conditions - Jaaffar, Nur Tasnem; Abdul Majid, Zanariah (Malaysian Mathematical Society, 2023)
This study applied direct block multistep method with strategy to reduce function call in order to solve Delay Differential Equation (DDE) with initial condition. This study solves constant and pantograph delay type where the proposed method uses the previous calculated solutions and apply Lagrange interpolation method for the respective types of delay. The development of the proposed method is based on the diagonally implicit strategy where the interpolation points are defined diagonally to reduce the function calls so that it will reduce the computational time. Several numerical examples are taken into consideration to check the credibility of our strategies.